Interaksi Fundamental ICR dan DER Terhadap Harga Saham Properti dengan Moderasi BI Rate - Inu Yuwan Fatoni; Mifta Hulaikah; Eryul Mufidah; Aris Zulianto (MARGIN ECO, 2026)
The property sector is an industry that is very sensitive to monetary policy, but share price dynamics often show anomalies relative to fundamental indicators in volatile market conditions. The novelty of this research lies in testing the Moderated Regression Analysis (MRA) model to reveal the extent to which monetary policy (BI Rate) is able to moderate the influence of internal financial fundamentals (ICR and DER) on stock prices amidst massive government fiscal intervention. Taking the focus on the property sector on the Indonesia Stock Exchange for the 2020-2024 period, the research sample was determined using a purposive sampling approach which produced 100 observation data. Empirical findings confirm that although the model is tested simultaneously feasible (Sig. 0.025), partially only the Debt-to-Equity Ratio (DER) has a significant negative impact on stock prices. On the other hand, the Interest Coverage Ratio (ICR) and BI Rate do not have a significant direct contribution. The crucial results of this research reveal that the BI Rate failed to play a moderating role, which indicates the existence of a "decoupling" phenomenon or a break in monetary policy transmission in the capital market. This proves practically that government stimulus policies (such as VAT DTP and LTV relaxation) as well as fixed interest debt structures for property issuers are much more dominant in reducing market sensitivity to interest rate fluctuations. This research provides a new contribution to the financial management literature by proving that in conditions of crisis or economic recovery, investors tend to ignore external monetary signals and consider real solvency risk (DER) as the main indicator of asset valuation.